The relationship between urbanisation and cross-national homicide rates: robustness across multiple estimation methods. Issue 3 (2nd July 2016) - Levchak, Philip J.
ABSTRACTS: Urbanisation has generally been found to be a non-significant predictor of homicide rates in cross-national studies. Despite this, there is strong theoretical support for the presence of a positive association between the two. The present study analyses data for up to 57 nations for the period 1993–2005 and examines the relationship between urbanisation and homicide using pooled ordinary least squares, feasible generalised least squares, panel-corrected standard errors, fixed-effects, and random-effects estimation. The results show that urbanisation is one of the strongest predictors of homicide in the cross-national context. This is consistent with the expected relationship according to modernisation theory and suggests that rapidly urbanising nations should be concerned with the unintended consequences of urbanisation.